Outcome of pregnancies after inadvertent exposure to GnRH agonist in early pregnancy. - Fatima, P; Hossain, MM; Rahman, D; Suman, GM (Mymensingh Medical Journal, 2011)
Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka